Circulating levels of inflammatory mediators in pregnant people living with HIV according to antiretroviral therapy regimen - Hindle, Stephanie; Girard, Sylvie; Cote, Helene C. F.; Money, Deborah; Mann, Evelyn; Boucoiran, Isabelle; , for the Children and Women Antiretroviral Therapy and Makers of Aging (Carma) Preg Team (Frontiers in Microbiology, 2024)
The use of antiretroviral therapy (ART) during pregnancy, particularly protease-inhibitor-based regimens (PI), has been linked to adverse outcomes including preterm delivery. As this outcome may be related to systemic inflammation, we sought to characterize inflammatory profiles of pregnant people living with HIV (PLWH) by comparing their levels of inflammatory mediators at two timepoints during pregnancy according to ART regimen, and to HIV-negative controls. Second and third trimester samples from 144 pregnant PLWH treated with ART and 24 HIV-uninfected controls were retrieved from the CARMA-PREG cohort. Peripheral plasma levels of 12 inflammatory mediators previously linked to HIV infection and/or poor pregnancy outcomes were quantified by multiplex assay: HMGB1, GM-CSF, IFNα, IFNβ, IFNγ, IL-10, IL-17, IL-1β, IL-6, TNFα, AGP, and CRP. Levels were compared by ART regimen and HIV status. Adjusted analyses showed that PLWH have higher levels of AGP throughout pregnancy and lower levels of IFNγ and IL-1β during the second trimester. PI-based regimens are associated with significantly higher levels of IFNα and IL-17 during the second trimester and IFNα, CRP, HMGB1, and IFNβ during the third trimester compared to InSTI-based regimens. The PI-subgroup was associated with preterm delivery and higher HIV-1 viral load. Our results suggest that PI-based regimens are associated with a pro-inflammatory and antiviral immunological response and a high viral load, which may be a mechanism through which PIbased regimens increase the risk of preterm delivery. Further investigations into cellular mechanisms and pro-inflammatory cascades leading to preterm delivery are necessary to support this association.